Overwinter body condition, mortality and parasite infection in two size classes of 0+ year juvenile European bitterling Rhodeus amarus - Francová, K; Ondračková, M (Journal of fish biology, 2013)
Body condition and parasite abundance were examined in two size classes of European bitterling Rhodeus amarus during the first overwintering period in two seasons (2007-2008 and 2009-2010). Body condition of large fish did not change during winter, and increased significantly in March. From November to February, small fish showed a decreasing trend in condition. Despite a significant increase in March condition of small fish only reached the same level as before winter. Total parasite abundance increased significantly in winter in both fish size classes, reflecting a seasonal increase in monogenean infection. Large fish were parasitized significantly more than small fish during winter, but only in small fish was a negative correlation between parasite infection and condition found and a significant decrease in parasite abundance recorded after wintering, indicating mortality of heavily infected individuals with low condition during the winter. A trend for higher overwinter mortality in small fish was found under semi-experimental conditions. The decrease in condition during the winter period in small fish may reflect faster energy depletion generally expected in smaller individuals. The results indicate that parasite infection may contribute to the overwinter mortality of 0+ year R. amarus, with a stronger effect in smaller individuals.
Keywords: nemoci ryb; Population Density; analýza přežití; Fish Diseases; Trematoda; hustota populace; Host-Parasite Interactions; Trematode Infections; infekce červy třídy Trematoda; tělesná konstituce; velikost těla; zvířata; Survival Analysis; Body Constitution; roční období; Seasons; Body Size; Animals; interakce hostitele a parazita; Cyprinidae